2016
DOI: 10.1038/srep18908
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Bacillus anthracis Live Attenuated Spore Vaccine Based on the htrA- (High Temperature Requirement A) Sterne Strain

Abstract: Anthrax is a lethal disease caused by the gram-positive spore-producing bacterium Bacillus anthracis. Live attenuated vaccines, such as the nonencapsulated Sterne strain, do not meet the safety standards mandated for human use in the Western world and are approved for veterinary purposes only. Here we demonstrate that disrupting the htrA gene, encoding the chaperone/protease HtrA (High Temperature Requirement A), in the virulent Bacillus anthracis Vollum strain results in significant virulence attenuation in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Involvement of HtrA BA in the resilience of the bacteria to stress was demonstrated previously by determining the growth of Δ htrA strains under various stress conditions and is considered to represent the main reason for the virulence attenuation associated with htrA gene disruption (Chitlaru et al, 2011b, 2016). To determine the relative contribution of the proteolytic or the PDZ domains to the role of HtrA BA in the resilience of the bacteria to stress, Δ HtrA trans -complemented with the FL, ΔPDZ or S255A forms of HtrA BA were subjected to a growth dilution drop-assay addressing sensitivity to high temperature, oxidative stress and salt, as depicted in Figure 4 (see also Supplementary Figure S3 for temperature sensitivity complementation using liquid cultures).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Involvement of HtrA BA in the resilience of the bacteria to stress was demonstrated previously by determining the growth of Δ htrA strains under various stress conditions and is considered to represent the main reason for the virulence attenuation associated with htrA gene disruption (Chitlaru et al, 2011b, 2016). To determine the relative contribution of the proteolytic or the PDZ domains to the role of HtrA BA in the resilience of the bacteria to stress, Δ HtrA trans -complemented with the FL, ΔPDZ or S255A forms of HtrA BA were subjected to a growth dilution drop-assay addressing sensitivity to high temperature, oxidative stress and salt, as depicted in Figure 4 (see also Supplementary Figure S3 for temperature sensitivity complementation using liquid cultures).…”
Section: Resultsmentioning
confidence: 89%
“…Anthrax is acknowledged as a toxinogenic disease, owing to the lethality of pure toxin preparations and pivotal role of the toxins in B. anthracis virulence, yet, during infection, B. anthracis secretes a large number of proteins, many of which bear biological functions indicative of a role in the onset and progression of the disease (Ariel et al, 2002, 2003; Chitlaru et al, 2006, 2007). As of today, a number of proteins, other than the classic toxins, have been suggested to play an essential role during B. anthracis infection, based on the attenuated virulence of null mutants entailing targeted disruption of specific genes (Chitlaru et al, 2011a; see Chitlaru et al, 2016 for a list and discussion of reported B. anthracis attenuating mutations).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic/serologic surveys of B. anthracis ( 1 3 ) showed that the secreted protease/chaperone high-temperature requirement (HtrA) (involved in protein synthesis quality control and necessary for tolerance to heat, oxidative, and other stress regimens) belongs to a class of immunogenic vaccine and disease biomarker candidates ( 4 ). Virulence-attenuating htrA gene disruption was implemented for the development of a live spore vaccine ( 5 7 ). Recently, we suggested that HtrA acts as both a protease/chaperone and a pleiotropic factor of gene expression ( 8 ).…”
Section: Announcementmentioning
confidence: 99%